Rigs-To-Reef (R2R): A new initiative on re-utilization of abandoned offshore oil and gas platforms in Indonesia for marine and fisheries sectors. (March 2019) - Nugraha, R B A; Basuki, R; Oh, JS; Cho, Il H; Naibaho, N; Secasari, Y; Mbay, LON
Abstract: Indonesia has more than 600s offshore oil and gas platforms spread in its territorial waters and of that amount, about 50 % were built around 1980s. Since the first generation platform was built almost half a century ago, decommissioning the offshore structures is something that has never been done before in Indonesia. The assets are now approaching their end of production and touching a point of minimum economic viability. Therefore, the dismantling of those structures is unavoidable issues in the near future. However, this process is not easy and presents many challenges, eg. status of assets, costs, etc. The current regulations have not been able to get the operators to dismantle and write off their assets so that many of them are left abandoned and endanger for the sea traffic for instance. There is a trend that these abandoned and idle offshore structures have now become "a fashionable donation" project from oil companies to coastal state to be re-used as artificial reefs or also known as Rigs-to-Reef (R2R). This study is attempting to improve the visibility of R2R as a potential decommissioning solution in Indonesia that provide good benefits not only for the environment but also for the coastal community while at the same time offer effective and efficient way out for oil and gas companies. The feasibility study of platform placement was done in the provincial marine conservation areas (Kawasan Konservasi Perairan Daerah, KKPD) in Bontang, East Kalimantan.